Linking Critical Zone With Watershed Science: The Example of the Heihe River Basin. Issue 11 (1st November 2022) - Li, Xin; Cheng, Guodong; Fu, Bojie; Xia, Jun; Zhang, Ling; Yang, Dawen; Zheng, Chunmiao; Liu, Shaomin; Li, Xiubin; Song, Changqing; Kang, Shaozhong; Li, Xiaoyan; et al.
Abstract: Watersheds are the basic unit of Earth's terrestrial systems and are therefore ideal units for the study of critical zones (CZs). However, grand challenges remain regarding the observation, modeling, and management of CZs and watershed systems. We synthesize the progress and breakthroughs associated with watershed science and CZ research in the Heihe River basin (HRB), a large‐scale endorheic river basin with unique mountain cryosphere‐oasis‐desert landscapes and prominent human‐nature competition for water resources. The HRB observation system consists of mountain cryosphere, agricultural oasis, and natural oasis observatories and is promoted by large‐scale comprehensive experiments to achieve multiscale observations. A watershed system model that couples ecohydrological models with socioeconomic models is developed to investigate the complex interactions among water, ecology, and socioeconomics in the HRB. The model is embedded in a decision support system to bridge science and decision‐making and to better serve river basin sustainability. Significant progress and breakthroughs have been made in CZ and watershed process research (e.g., cryospheric hydrological processes, ecological and hydrological interactions, and surface‐groundwater interactions) in the HRB. Nevertheless, observation and modeling of geochemical and geomorphological processes in the CZ have not been well addressed in integrated watershed studies of the HRB. In the future, new observation technologies, agent‐based models, machine learning, and data assimilation will benefit both watershed science and CZ science and help to address complexity and dynamics in the CZ at the river basin scale. Overall, the HRB has successfully demonstrated how an experimental river basin can link CZ science with watershed science. Key Points: Progress and breakthroughs associated with watershed science and critical zone (CZ) research in the Heihe River basin (HRB) are reviewed and synthesized The observation system, model, and decision support system of the HRB contribute to new findings on the watershed and CZ processes Linking critical zone science with watershed science can achieve a better understanding of the Earth system